Occupational stress among overweight and obese workers in a medical devices industry and an intervention program / Norhafizah Mohd Hassan - Mohd Hassan, Norhafizah (2012)
Objective: To examine a possible association between overweight/obese workers and occupational stress in a Medical Devices Industry and also carried out an intervention program. Method: Part One: A questionnaire on job stress and eating behavior was distributed among 87 overweight and obese workers from the factory. Part Two: An intervention program encompassed of dietary plan and physical activity programs (aerobic exercise) were conducted, 40 overweight and obese workers were volunteered to participate in the program which the primary focuses of the program is a weight loss and stress reduction. The relation between overweight/obesity, job stress, and eating behavior were analyzed using descriptive analyses (crosstab). The paired t test was used to determine BMI differ before and after intervention program and using descriptive analyses to look at the effectiveness of the program to reduce stress at work.Results: Overweight and obese workers were associated with several elements in occupational stress especially social support, physical environment and mental demands. The eating behaviors were linked with the subjects. Besides, in this study found that the intervention programs achieve modest improvements in participants' weight status at the 3 months however their level of stress were significantly reduced. Conclusion and Recommendations: The study suggests that overweight/obese workers tend to be in a stressful state from high job demands, in-conducive environmental workplace and lack of social support from the top managers. Such stressful conditions may affect eating behaviors to eat much and contribute to obesity. The findings of this study also can help inform decisions of employers that worksite nutrition and physical activity programs to promote healthy weight and stress management among workers are necessary in the workplace.